Mempersiapkan Dokumen Lamaran Kerja Dan Wawancara Kerja Bagi Siswa-Siswi Sekolah Menengah Kejuruan - Francisca Hermawan; Andreas Elang Detra (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2021)
The Training with the topic of Preparing Job Application Documents and Job Interview for Vocational High School Students played important role for the graduated students empowered by Bulir Padi to apply for job and get jobs according to their competencies. Due to the Covid-19 pandemic the training was carried out using zoom application. It was on July, 14, 2020. The training was presented by the team of FEB UAJ. The methods used in the process were lecturing, simulation and discussion. The material in the first session was Motivation. Session two was themed with How To Compose A Professional Curriculum Vitae, and the third session was Tips for Successfully Facing Job Interviews. The evaluation showed that although the training was in short it fairly succeeded in developing more confidence of the participants to prepare themselves to enter the world of work. This was shown by numerous students who asked questions, gave comments and were engaged during job interview simulation session.